PEMBELAJARAN PENDIDIKAN JASMANI ADAPTIF BERBASIS MUSIK DAERAH PADA SENAM AEROBIK - Fauqi, Amal (Lembaga Penelitian dan Pendidikan Mandala, 2022)
Research has been carried out on the Development of Adaptive Physical Education Learning Devices on the material of Aerobic Gymnastics Based on Local Culture